Physicochemical and microbiological properties of longan, bitter bush, sunflower and litchi honeys produced by Apis mellifera in Northern Thailand - Wanjai C. (2014)
Forty two monofloral honey samples which were derived from four botanical sources of Longan (Dimocarpus longan Lour.), Bitter Bush (Eupatorium odoratum Linn.), Sunflower (Helianthus annuus Linn.), and Litchi (Litchi chinensis Sonn.) were collected from apiaries in Northern Thailand. Physicochemical properties (i.e. moisture, ash, pH, total acidity, diastase activity, electrical conductivity, major carbohydrates, and hydroxymethylfurfural) and total microbial counts (aerobic mesophilic bacteria, yeasts, and moulds) were studied according to AOAC methods. Although the physicochemical parameters of the honey samples were varied, most of the honey samples were in the acceptable range of international standards. The numbers of aerobic mesophilic bacteria and of yeasts and moulds were estimated for each sample to determine microbiological quality. Total bacterial counts ranged from 0-400 cfu/g and total fungal counts were 0-333 cfu/g. The Thai honeys tested conformed to the international honey standards. © IBRA 2012.